Comparing quantitative and qualitative verbal and social autopsy tools: does a qualitative supplement improve understanding of the social determinants of under-five deaths in the slums of Kampala, Uganda? - Amy W Blasini; Peter Waiswa; Ann Wolski; Phillip Wanduru; Chelsea Finkbeiner; Ashura Bakari; Lucky Amutuhaire; Cheryl A Moyer (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Understanding biological causes of death and sociocultural factors influencing outcomes is critical to reducing mortality in low-resource settings. Verbal and Social Autopsy instruments (VASAs) query family members about events leading to an individual's death, resulting in quantitative, categorical data. This study sought to determine the value of a supplemental in-depth qualitative interview (VASA-QUAL). # Methods This cross-sectional study was conducted in two slum neighborhoods in Kampala, Uganda, among families who lost a child under five within the preceding six months. A trained, local researcher conducted the quantitative VASA and then administered the VASA-QUAL to family members. Quantitative data were analyzed using Stata V16.0; qualitative data were transcribed into English and analyzed using NVivo V12.0. The biomedical cause of death was determined using a panel of physicians to code verbal autopsy items. Quantitative VASA variables were compared with qualitative variables from the VASA-QUAL using a rubric of indicators derived from the Pathways to Survival framework. Kappa statistics and percent agreement were calculated to compare quantitative and qualitative data. Three coders independently rated whether qualitative data provided additional information that improved understanding of the cause of death. # Results 48 VASAs were conducted (child age range: 1 month to 52 months). Agreement on key indicators ranged from 81.2% (place of death) to 93.8% (recognition of illness), with Kappa coefficients ranging from -0.038 to 0.368. The qualitative component added or clarified information about pediatric illness and care-seeking across all indicators, including recognition of illness (94.0%), care-seeking decisions (79.0%), whether home care was provided (73.0%), and choice of outside care (85.0%). Qualitative interviews frequently included symptoms missing or denied in the quantitative VASA and clarified the chronological order of symptoms. Many qualitative interviews described complicated mechanisms of decision-making not captured in the quantitative survey. Both agreement across data types and whether meaningful information was added by the qualitative data varied by cause of death, although our sample size limited our ability to conduct statistical analysis in this regard. # Conclusions Supplementing quantitative VASA tools with an in-depth VASA-QUAL interview provided important additional information, but not consistently across indicators or causes of death. Despite challenges associated with feasibility, supplemental qualitative interviews may be an important tool for understanding the complexity of events leading up to childhood deaths.